Methodical features of formation of cognitive universal educational actions in schoolchildren - Maleeva E. V. (Pedagogy and psychology: development prospects, 2018)
The article discusses the methods and methods of organization of educational activities of schoolchildren aimed at the development of cognitive universal educational activities, recommendations to teachers to create educational motivation in the classroom.
Keywords: универсальные учебные действия; учебная мотивация; учебная деятельность; Universal educational actions; educational activity; учебная задача; educational motivation; educational task